Sustainable participation behaviour in agri-environmental measures - İlkay Unay-Gailhard; Štefan Bojnec (Journal of Cleaner Production, 2016)
In recent years, studies have identified the determining factors for participation in voluntary agri-environmental measures (AEMs) by farmers who support sustainable agricultural production practices. Although the previous implementation of AEMs is an important determinant of sustainable behaviour, attempts to investigate the forces driving this long-term behaviour are scarce. This study aims to provide empirical insights into which determinants of probability of sustainable behaviour are associated with AEM participation by Slovenian farmers. Particular attention is given to the drivers of farm and farmland use characteristics. The data used are taken from the Farm Accountancy Data Network for the 2004–2010 period. Logit regressions for Markov transition probability models and a long-term sustainable participation behaviour model are used to explore the existence of distinct characteristics of AEM participation for different sub-periods. The empirical results confirmed that different drivers are associated with sustainable behaviour across time periods and farm types. Land productivity, capital intensity and farm size have significant effects on the probability that a farmer will consistently participate in the AEM programme for at least 5 year period. These findings suggest that farm-specific characteristics are the primary drivers of sustainable behaviour associated with AEM participation.
Keywords: 330; Agri-environmental measures; Sustainable participation behaviour; Markov transition probability model; Logit regression; Farm Accountancy Data Network (FADN) dataset; Slovenia